A study on localised corrosion inhibition by organic molecules - Tan, Y.; Mocerino, Mauro; Paterson, T.; Morley, D. (2011)
Laboratory experiments have been carried out to investigate the corrosion inhibiting behaviour of resorcinarene derivatives, a carboxylic acid and an amide/amine, using an electrochemically integrated multi-electrode array namely the wire beam electrode. The resorcinarene derivatives effectively inhibited uniform and localised steel corrosion in carbon dioxide saturated brine solutions. The inhibition of localised corrosion appears to be due to the creation of a large number of minor anodes randomly distributing over the wire beam electrode surface, leading to insignificant general anodic dissolution.